(3JMdjd GdGSJKeGQ GdeGdj (B:s (3GdCOhGJ hGdJehjd hGdeNGWQ(B/s - (3Jhajb, eMH NdIs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj WHY, fTQ, JhRjY,s, 2022)
(3eQJaY Ch QDi JLGQjI ZjQ YGOjI Ch eYdheGJ OGNdjI eJejRg, GfeG eG jMJGLg gh GWGQ acQj Sdje dGJNGP GdbQGQGJ hGdbOQGJ Ydi cHM GdYhGWa hGdGfMjGR GHGf GdeYGedGJ GdGSJKeGQjI MJi dG jJGcd gPG GdGWGQ GdacQj(B. (3hHGJ GdJehjd bQjf GdGSJKeGQ hef ZjQ GdeHQQ WdH GdJehjd Ohf hLhO NWW GSJKeGQjI dGSJjHYGHg, ceG jSJMjd GdONhd aj GdGSJKeGQ Ohf Cf jJhGaQ dgG GdJehjd ShGA cGf PGJjG aj GdeYGedGJ GdaQOjI Ch Mbhb GdedcjI aj eYGedGJ efXeGJ GdCYeGds
(3HHdjhLQGajI (B: (3UaMI (B301-304.s
Keywords: (3GdEOGQI GdeGdjIs; (3GdeGdjIs -- (3JMdjds; (3GdGSJKeGQs -- (3EOGQIs